‘Let's work together to pass medical school’: a qualitative study of medical student attitudes to teamwork, competition and collaboration - Helen R. Watson; Paul Millin; James Close; Robert Jeffery; Holly Stephenson; Daniel Zahra (FEBS Open Bio)
Teamwork is vital to all types of work, and graduates of higher education programmes must be prepared to contribute to a wide variety of professional teams. This is especially true in healthcare, where graduates will work in multidisciplinary teams (MDTs) under considerable pressure. This study is a follow‐up to a previous study, where we described how competition between students is a barrier to constructive teamwork. Since then, we have made considerable enhancements to our transferable skills curriculum, moved away from norm referencing, and there have been national changes to the way that graduate Foundation training places are allocated. Here we present findings from a qualitative study of students from all six stages of our medical degree programme (5 years plus predegree foundation year). We explored whether there had been changes in how students perceived the importance of teamwork, their own teamwork development and how they collaborated with their peers. Following analysis of in‐depth, semi‐structured interviews, five themes emerged: (a) competition between students; (b) importance of teamwork; (c) what makes effective teamwork; (d) preparing for work in MDTs; and (e) recommendations for teamwork education. Competition between students was perceived as both positive and negative, but there has been a shift since our last study towards collaboration, with students now more willing to help each other succeed. Students also show more insight into their teamwork development, and were able to discuss what aspects of the programme, and higher education more broadly, were most valuable in helping them develop.